Going against the grain. Issue 4 (5th December 2018) - Hannan, Shauna
Abstract: The following creative non‐fiction essay describes the author's process of building her own casket as a gift to her family. In addition to being a practical piece of furniture for the time being (presently serving as a bookshelf), the casket has been a popular conversation piece and teaching tool. Even more, it is a regular reminder of mortality and, therefore, a call to live fully and faithfully each day. The essay is a reflective piece prompted by the casket itself.